Detecting miRNAs expression as the early prognostic factor for patients with colorectal cancer in Dr. Sardjito Hospital Yogyakarta : A preliminary study - Adeodatus Yuda Handaya; Didik Setyo Heriyanto; Hendra Susanto; Yudi Susanto; Kamal Agung Yudayana; Ida Ayu Setyawati Sri Krisna Dewi; Aditya Rifqi Fauzi; Joshua Andrew; Kevin Radinal; Azriel Farrel Kresna Aditya (Faculty of Medicine, Universitas Islam Indonesia, 2023)
Background: Colorectal cancer (CRC) is the third highest-ranked cancer and causes high mortality in patients with a low survival rate. The lack of sensitivity and specificity of clinical and other diagnostic modalities results in a higher mortality rate. Therefore, the exploration of potential early biomarkers for CRCs is necessary.Objective: We aimed to evaluate the local expressions of potential tumor suppressor and oncogenic miRNAs in CRC patients in Indonesia. Methods: This retrospective cohort study involving thirty-one colorectal carcinoma patients at Dr. Sardjito Hospital Yogyakarta from January 2014-December 2017. Total RNA was isolated, and the expressions of miR-21, miR-92a, miR-96, miR-26b, miR144, and miR-195 were measured by real-time quantitative PCR. The correlation between miRNAs and other predictors was determined by Spearman correlation, and the association of miRNA expression and other clinical parameters used logistic regression.Results: The local expression of miR-195 decreased significantly in the tumor sites. In contrast, miR-21 activity tends to increase in the local tumor. Meanwhile, the expressions for miR-92a, miR-96, miR26b, and miR-144 in the same subjects were non-significant. MiR-195 was also significantly associated to cancer stage (r=-0.570, p=0.001) with significant odds ratio (OR=0.892, 95% CI=0.804–0.990, p=0.031).Conclusion: Our study was the first to report aberrant expressions of miRNA-21, miRNA-195, miRNA-92a, miRNA-26b, miRNA-96, and miRNA-144 in Indonesian CRC patients. The tumor suppressor miRNA-195 expression was superior among others to serve as an early biomarker in detecting and predicting CRC disease progression.